Clinical features of the acute period of myocardial infarction with ST segment elevation in patients after reperfusion therapy - S. M. Kyselov; Yu. V. Savchenko (Zaporožskij Medicinskij Žurnal)
Aim: to determine the clinical features of the course of myocardial infarction with ST segment elevation in the acute period in patients after reperfusion therapy.